Tris(1,3-dichloro-2-propyl) phosphate disrupts dorsoventral patterning in zebrafish embryos - Dasgupta, Subham; Vliet, Sara M.; Kupsco, Allison; Leet, Jessica K.; Altomare, Diego; Volz, David C. (PeerJ, 2017)
Tris(1,3-dichloro-2-propyl) phosphate (TDCIPP) is a high-production volume organophosphate flame retardant widely used within the United States. Within zebrafish, initiation of TDCIPP exposure at 0.75 h post-fertilization (hpf) results in genome-wide alterations in methylation during cleavage (2 hpf) as well as epiboly delay or arrest (at higher concentrations) during late-blastula and early-gastrula (4–6 hpf). To determine whether these TDCIPP-induced effects were associated with impacts on the transcriptome, embryos were exposed to vehicle (0.1% DMSO) or 2 µM TDCIPP from 0.75 hpf to 6 hpf, and total RNA was extracted from triplicate embryo pools per treatment and hybridized onto duplicate Affymetrix Zebrafish Gene 1.0 ST Arrays per RNA sample. Based on transcriptome-wide profiling, TDCIPP resulted in a significant impact on biological processes involved in dorsoventral patterning and bone morphogenetic protein (BMP) signaling. Consistent with these responses, TDCIPP exposure also resulted in strongly dorsalized embryos by 24 hpf—a phenotype that mimicked the effects of dorsomorphin, a potent and selective BMP inhibitor. Moreover, the majority of dorsalized embryos were preceded by epiboly arrest at 6 hpf. Our microarray data also revealed that the expression of sizzled (szl)—a gene encoding a secreted Frizzled-related protein that limits BMP signaling—was significantly decreased by nearly 4-fold at 6 hpf. Therefore, we used a splice-blocking morpholino to test the hypothesis that knockdown of szl phenocopies TDCIPP-induced delays in epiboly progression. Interestingly, contrary to our hypothesis, injection of szl MOs did not affect epiboly progression but, similar to chordin (chd) morphants, resulted in mildly ventralized embryos by 24 hpf. Overall, our findings suggest that TDCIPP-induced epiboly delay may not be driven by decreased szl expression, and that TDCIPP-induced dorsalization may—similar to dorsomorphin—be due to interference with BMP signaling during early zebrafish development.
Keywords: TDCIPP; Zebrafish; Dorsoventral patterning; Embryo; Flame retardant; Public health